Pembinaan Rohani dan Mental Tahanan di Rumah Tahanan Polda Kalimantan Barat: Upaya Rehabilitasi Holistik Berbasis Komunitas - Annisa; Husni, Muhammad (Belalek, 2025)
This community service program was implemented to address the spiritual and psychological needs of detainees at the West Kalimantan Regional Police Detention Center, who commonly experience emotional distress, limited positive activities, and insufficient access to religious guidance or mental support. The program employed an integrative approach that combined spiritual interventions including Qur’an recitation, supplication, reflective discussions, and religious study with mental health techniques such as group counseling, stress management, and relaxation exercises. Data were collected through observation, interviews, and participant engagement assessments. The results indicate significant improvements in religious awareness, worship discipline, emotional stability, and stress regulation. Detainees also demonstrated positive behavioral changes, including heightened empathy, cooperation, and motivation for self-improvement. These findings highlight that structured spiritual and mental guidance effectively enhances detainees’ spiritual well-being and psychological resilience while fostering a more supportive social environment. The program is recommended for ongoing implementation as a humanistic, Islam-based rehabilitation model within the police detention system.